2019
DOI: 10.1021/acsabm.9b00746
|View full text |Cite
|
Sign up to set email alerts
|

Microcarriers with Controllable Size via Electrified Liquid Jets and Phase Separation Technique Promote Cell Proliferation and Osteogenic Differentiation

Abstract: Differently sized poly(lactic-co-glycolic) microspheres were efficiently prepared with electrified liquid jets and a phase separation technique for a wide range of applications. Higher polymer concentrations tended to form larger microcarriers. Polymer concentration can obviously affect bead or fiber formation resulting beads and fiber morphologies. As the voltage of electrostatic field and the needle size increased, the size of microcarriers decreased remarkably. The most suitable concentration of ethanol in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 28 publications
3
8
0
Order By: Relevance
“…In the present study, the surface of the composite microspheres became rough due to the incorporation of nBM. In Jiao's report, the surface of composite microcarriers with nHA was rougher than that of PLGA observed by ESEM 27 . This was consistent with our study.…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…In the present study, the surface of the composite microspheres became rough due to the incorporation of nBM. In Jiao's report, the surface of composite microcarriers with nHA was rougher than that of PLGA observed by ESEM 27 . This was consistent with our study.…”
Section: Resultssupporting
confidence: 92%
“…The particle sizes of the microspheres were not strictly uniform, but were normally distributed. Therefore, the settling volume of microspheres was used for the quantification of microspheres in vitro and vivo studies as previously reported 22,27,28 . First, the microspheres were immersed in PBS.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The phase separation of LLPS microcarriers in an aqueous solution, results in the production of discrete liquid phases, with differing compositions. This enables the encapsulation of various bioactive compounds, such as proteins and growth factors, in various phases of the microcarrier [ 15 , 16 ]. Cell harvesting from substrates is challenging in conventional microcarrier systems, because it requires enzymatic treatment, which is frequently paired with agitation.…”
Section: Introductionmentioning
confidence: 99%